Identification and management of seizures in children - Harasani, Mohammed Khalid; Alanazi, Wael Khulaif; Aloqbi, Hanan Saleh; Hijazi, Maiar Najeeb; Alrashed, Shahad Khaled; Albalawi, Nouf Nasser; Alharbi, Awad Saeed; Alsibyani, Randa Mohammed; Alharbi, Abdulaziz Abdullah; Alqahtani, Bader Abdulaziz; Alaliwat, Ghadeer Ali (International Journal Of Community Medicine And Public Health, 2022)
Estimates from epidemiological studies indicate the high global prevalence of seizures in children. They can be associated with different complications that might even be life-threatening. Different risk factors have been reported to increase the risk and severity of seizures, like metabolic disorders, infections, and reduced access to needed care. Therefore, providing appropriate management is essential to enhance the prognosis of these cases. In the present article, we conducted a literature review to shed more light on identifying, diagnosing, and managing seizures in children. The identification process depends on different factors, including obtaining an adequate history from the patient or their caregivers, performing a thorough general and neurological examination, and conducting appropriate investigations whenever needed. It should be noted that in severe cases, these approaches should be made promptly not to delay the management approaches, which can be life-saving. Reassuring family attendants is also recommended. Besides, increasing awareness among these families about the diagnosis, identification, prognosis, reporting, and responding to seizures might reduce the risk of recurrence and enhance the prognosis of seizures. Choosing a treatment strategy is usually based on different factors, including the child’s age, epilepsy type, family preferences, the presence of comorbidities, and ability to administer medications. For recurrent seizures, home-based medications, like rectal diazepam or buccal midazolam, might also be used to lower the risk of recurrence and reduce the intensity of seizures.